2002
DOI: 10.1007/s00427-002-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterisation of PKB and PRK homologs from Hydra and the evolution of the protein kinase family

Abstract: Two new serine/threonine protein kinases have been cloned from Hydra cDNA. The first of these kinases belongs to the PKB/Akt family. It is expressed ubiquitously in Hydra at a relatively low level but is upregulated during head regeneration. The second kinase is a member of the PRK/PKN family. It is ubiquitously expressed in Hydra tissue, albeit at a higher level than PKB. Construction of a phylogenetic tree including the Hydra PRK and PKB kinases and two PKC homologs previously cloned by Hassel and comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Furthermore, it is likely from the phylogenetic tree that atypical PKC was first formed by evolution from the common prototype of the AGC protein kinase family, and novel and conventional PKCs next. The relationships among mammalian PKC isoforms and PRKs 28) and that between conventional and novel PKCs and other protein kinase family have been discussed by other investigators as well, [29][30][31] and are consistent with the phylogeny of the protein kinase catalytic domains shown in Fig. 5.…”
Section: Evolutionary Relationships Of Pkc Isoformssupporting
confidence: 83%
“…Furthermore, it is likely from the phylogenetic tree that atypical PKC was first formed by evolution from the common prototype of the AGC protein kinase family, and novel and conventional PKCs next. The relationships among mammalian PKC isoforms and PRKs 28) and that between conventional and novel PKCs and other protein kinase family have been discussed by other investigators as well, [29][30][31] and are consistent with the phylogeny of the protein kinase catalytic domains shown in Fig. 5.…”
Section: Evolutionary Relationships Of Pkc Isoformssupporting
confidence: 83%
“…An insulin receptor homolog was cloned [63] and three insulin genes have now been identified (Steele, personal communication). It was shown that protein kinase B in Hydra has all the characterisitics to be regulated by PI(3)kinase signalling [64] and that the PI(3) kinase inhibitor wortmannin induces massive apoptosis in Hydra [65]. When a Hydra FoxO-GFP fusion protein is expressed ectopically in Hydra epithelial cells, it is partially translocated into the nucleus due to the GFP-tag [57,66].…”
Section: Hydra Insulin Signalling In Apoptosis Regulationmentioning
confidence: 98%
“…In fact, evolutionary studies indicate that Pkns and PKCs have a common evolutionary ancestor (Herold et al 2002). In yeast, a single PKN/PKClike molecule exists that has domains similar to the ACC domains of Pkn and to the C1 and C2 domains of PKCs.…”
Section: Rho Gtpase Binding Is Required For Efficient Pkn Function Dumentioning
confidence: 99%